Implementasi Budaya Literasi di MTs Negeri 3 Pamekasan dan MTs 1 Putri An-Nuqayah Sumenep: Strategi, Dampak, dan Tantangan - Kamilah, Kamilah; Sa’diyah, Halimatus (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Literacy culture is a means to develop the ability to find, evaluate, and utilize information in students from an early age. Through literacy culture in educational institutions, the quality of learning will be of higher quality because it can develop reading and writing skills and increase students' motivation to learn. In addition, the literacy culture applied is also a facility in developing students' ability to manage information so that learning becomes more meaningful, quality and fun. Therefore, both MTs. Negeri 3 Pamekasan and MTs. 1 Putri An-Nuqayah Sumenep institutions implement a literacy culture